Dose effects of a DNA vaccine encoding immobilization antigen on immune response of channel catfish against Ichthyophthirius multifiliis. Issue 106 (November 2020) - Xu, De-Hai; Zhang, Dunhua; Shoemaker, Craig; Beck, Benjamin
Abstract: Channel catfish ( Ictalurus punctatus ) vaccinated with pcDNA3.1-IAg52b plasmid DNA vaccine encoding immobilization antigen genes of Ichthyophthirius multifiliis (Ich) produced anti-Ich antibodies and were partially protected (20% survival) in a previous study. Here we evaluated whether a higher dose or two doses of pcDNA3.1-IAg52b vaccine could provide better protection for catfish against Ich. Fish were distributed into 6 groups and vaccinated using following schemes: 1.10 μ g pcDNA3.1-IAg52b fish −1, 2.20 μ g pcDNA3.1-IAg52b fish −1, 3. two doses of 10 μ g pcDNA3.1-IAg52b fish −1 with 7 days between doses, 4.20 μ g pcDNA3.1 fish −1 (mock-vaccinated control), 5.15, 000 live theronts fish −1 (positive control), and 6. non-vaccinated and non-challenge control. Parasite infection levels, serum anti-Ich antibody levels, fish mortality and immune-related gene expression were determined during the trial. Fish vaccinated with a single dose of 20 μ g pcDNA3.1-IAg52b fish −1 or two doses of 10 μ g fish −1 had higher anti-Ich antibody levels than fish receiving a single dose of 10 μ g fish −1 . Survival was significantly higher in fish receiving 20 μ g vaccine fish −1 (35.6%) or 2 doses of 10 μ g fish −1 (48.9%) than fish injected with a single dose of 10 μ g fish −1 (15.6%) or mock-vaccinated control (0%). Fish vaccinated at the dose 20 μ g fish −1 had higher expression of vaccine DNA in muscle than fish vaccinated with 10 μ g fish −1 . Fish vaccinated with the DNA vaccine showed higher up-regulation than mock-vaccinated control in the expression of IgM, CD4, MHC I and TcR-α genes during most of time points after vaccination. Further studies are needed to improve efficacy of DNA vaccines by using multiple antigens in the DNA vaccines. Highlights: Vaccinated fish showed higher anti-Ich antibody and survival than control fish. Fish had higher vaccine DNA expression when vaccinated 20 μ g than 10 μ g per fish. Fish had higher survival when received 20 μ g DNA vaccine than 10 μ g per fish. Fish vaccinated with DNA vaccines increased immune gene expression.